2021
DOI: 10.3389/fnins.2021.631852
|View full text |Cite
|
Sign up to set email alerts
|

In silico Analysis of Polymorphisms in microRNAs Deregulated in Alzheimer Disease

Abstract: BackgroundAlzheimer’s disease (AD) is a degenerative condition characterized by progressive cognitive impairment and dementia. Findings have revolutionized current knowledge of miRNA in the neurological conditions. Two regulatory mechanisms determine the level of mature miRNA expression; one is miRNA precursor processing, and the other is gene expression regulation by transcription factors. This study is allocated to the in-silico investigation of miRNA’s SNPs and their effect on other cell mechanisms.MethodsW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…We predicted and calculated the minimal free energies of the secondary structures of miR-3976 bounding to the CD147 3′-UTR containing T/C variant (rs6757) by computational modeling. The minimal folding energy and the ΔΔG value were used to assess the impact of SNPs on the binding ability of the miRNA with its target mRNA [ 22 ]. The minimal folding energies of the duplexes rs6757-T-containing (− 24.7 kcal/mol) is lower than that of the duplexes rs6757-C-containing (− 20.2 kcal/mol).…”
Section: Discussionmentioning
confidence: 99%
“…We predicted and calculated the minimal free energies of the secondary structures of miR-3976 bounding to the CD147 3′-UTR containing T/C variant (rs6757) by computational modeling. The minimal folding energy and the ΔΔG value were used to assess the impact of SNPs on the binding ability of the miRNA with its target mRNA [ 22 ]. The minimal folding energies of the duplexes rs6757-T-containing (− 24.7 kcal/mol) is lower than that of the duplexes rs6757-C-containing (− 20.2 kcal/mol).…”
Section: Discussionmentioning
confidence: 99%
“… 26 Generally, each miRNA can regulate various target genes and the polymorphisms in their target-binding site can have 3 outcomes, which include (1) neutral, (2) gain of novel targets, or (3) the loss of the original target. 6 , 27 Thus, a change in the binding site of miRNAs to their target genes or proteins alters the miRNA function; moreover, it alters their expression pattern by affecting the promoter area. 6 , 27 , 28 Labib et al showed that genotyping miRNA-146a polymorphism (rs2910164) and its target gene IRAK1 (rs3027898) was significantly correlated with susceptivity, clinical manifestations, and progressive condition in patients with systemic lupus erythematosus (SLE) and MS.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 27 Thus, a change in the binding site of miRNAs to their target genes or proteins alters the miRNA function; moreover, it alters their expression pattern by affecting the promoter area. 6 , 27 , 28 Labib et al showed that genotyping miRNA-146a polymorphism (rs2910164) and its target gene IRAK1 (rs3027898) was significantly correlated with susceptivity, clinical manifestations, and progressive condition in patients with systemic lupus erythematosus (SLE) and MS. Hence, it seems possible that rs2910164 polymorphism is involved in patients’ susceptibility to SLE and MS. 29 The previous publication revealed that interleukin-1 receptor–associated kinase 1 (IRAK1) could act as a potential target of miR-146a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, the development of large-scale genome wide analysis techniques has offered novel insights into the role of miRNA gene polymorphisms in the development of neurological disorders such as Tourette syndrome 21 . Mutations within a miRNA gene may affect different stages of its transcript processing and may result in abrogated miRNA function 22 . In AD, the presence of rs2910164 within MIR146A resulted in decreased levels of miR-146a-5p, correlating with increased levels of TLR-2, a critical microglial receptor mediating neuroinflammation following its binding to Aβ42 23, 24 .…”
Section: Introductionmentioning
confidence: 99%